Study on Central Provident Fund (CPF) and alternative retirement vehicles - Mah, Huimin (2008)
To examine the adequacy of Supplementary Retirement Schemes (SRS) and investment in annuity plans as a complement. We first outline the recent changes in CPF, followed by an analysis of its effect on Singaporeans. We further demonstrate the different roles of SRS and annuity plans played in one’s retirement planning.